ENERGI NUKLIR SEBAGAI SOLUSI UNTUK MENGHAMBAT PEMANASAN GLOBAL - Finahari, Ida Nuryatin (Jurnal Rekayasa Lingkungan)
Global warming is the increase in the average temperature of the earth surface, atmosphere and oceans.The global warming in recent years has been international issues. The issues come to the surfacebecause global warming has the very big impact to the world and the lives of animal, plant and human,such as world climate change. The main cause of global warming is the combustion of fossil fuel suchas coal, oil and natural gas, that released carbon dioxide and other gases to atmosphere as greenhousegases. One of alternative to retard this global warming is by replacing fossil fuel with utilization of nuclearenergy for power plant. As a comparison, a 1,000 MWe nuclear power plant as a substitute for coal fi redpower plant at the same capacity, will reduce 6,000,000 tons of CO2 gas emission per year. Consideringenvironmental aspect, the nuclear power plant is not emitting CO2 gas, so that the use of nuclear powerplant can retard the global warming. Considering economic aspect, based on operational experienceof nuclear power plants in advanced countries, it is shown that cost of generating electricity of nuclearpower plants is more competitive than fossil fuel power plant. Considering safety aspect, nuclear powerplant operating in the world, have passed by a technological test. They have also an excellent operationreliability and a very good safety system.